Acute severe male hypo-testosteronemia affects central motor command in humans. (June 2016) - Felici, Francesco; Bazzucchi, Ilenia; Sgrò, Paolo; Quinzi, Federico; Conti, Alessandra; Aversa, Antonio; Gizzi, Leonardo; Mezzullo, Marco; Romanelli, Francesco; Pasquali, Renato; Lenzi, Andrea; Di Luigi, Luigi
Abstract: Purpose: To indirectly evaluate the effect of androgens on neuromuscular system in humans we analyzed if an induced short-term hypogonadal state (serum total testosterone-TT < 2.3 ng/ml) may affect central drive to skeletal muscle and/or muscle neuro-mechanical performance. Methods: We compared voluntary and electrically evoked muscle sEMG signals from biceps brachii in nine hypogonadal male volunteers (Hypo) and in ten healthy controls (Cont). Serum TT and dihydrotestosterone (DHT) were assayed. Results: With respect to Hypo, Cont exhibited significantly higher median frequency content (MDF) at any angular velocity; normalized MDF [95.9% (SD = 23.3) vs 73.8% (SD = 9.3)]; muscle fiber conduction velocity (CV) from lowest to highest angular velocities; initial MDF at fatigue test [91.78 Hz (SD = 22.03) vs 70.94 Hz (SD = 11.06)] as well as was the normalized slope [−0.64 (SD = 0.14 vs −0.5 (SD = 0.11)]. In the non-fatigued state, Hypo showed a slower single twitches time to peak (TTP). In Cont, half relaxation time (HRT) decreased after fatigue while increased in Hypo ( p  < 0.05 between groups). A significant correlation between both TT and dihydrotestosterone with MDF and CV was found during voluntary contractions only. Conclusions: A brief exposure to very low serum TT concentration in males seem to determine a reduced excitability of the NM system which, in turn, would favor a predominant recruitment of slow twitch MUs.